Anesthetic Management of a Child with Mitochondrial Neurogastrointestinal Encephalopathy - Vianey Q. Casarez; Acsa M. Zavala; Pascal Owusu-Agyemang; Katherine Hagan (Case Reports in Anesthesiology)
Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is an autosomal recessive disorder associated with deficiency of thymidine phosphorylase (TP). Associated manifestations include visual and hearing impairments, peripheral neuropathies, leukoencephalopathy, and malnutrition from concomitant gastrointestinal dysmotility and pseudoobstruction. Given the altered metabolic state in these patients, specific consideration of medication selection is advised. This case report will describe the anesthetic management used in a 10-year-old girl with MNGIE. She had multiple anesthetics while undergoing allogeneic hematopoietic stem cell transplantation. This case report will discuss the successful repeated use of the same anesthetic in this pediatric patient, with the avoidance of volatile anesthetic agents, propofol, and muscle relaxant.